Anatomy imaging and hemodynamics research on the cerebral vein and venous sinus among individuals without cranial sinus and jugular vein diseases - Liu, Lu; Wu, Yan; Zhang, Kaiyuan; Meng, Ran; Duan, Jiangang; Zhou, Chen; Ji, Xunming (Frontiers in Neuroscience, 2022)
In recent years, imaging technology has allowed the visualization of intracranial and extracranial vascular systems. However, compared with the cerebral arterial system, the relative lack of image information, individual differences in the anatomy of the cerebral veins and venous sinuses, and several unique structures often cause neurologists and radiologists to miss or over-diagnose. This increases the difficulty of the clinical diagnosis and treatment of cerebral venous system diseases. This review focuses on applying different imaging methods to the normal anatomical morphology of the cerebral venous system and special structural and physiological parameters, such as hemodynamics, in people without cranial sinus and jugular vein diseases and explores its clinical significance. We hope this study will reinforce the importance of studying the cerebral venous system anatomy and imaging data and will help diagnose and treat systemic diseases.